Controlled field effect surface passivation of crystalline n-type silicon and its application to back-contact silicon solar cells - Bonilla, R; Reichel, C; Hermle, M; Senkader, S; Wilshaw, P (Institute of Electrical and Electronics Engineers Inc., 2014)
Surface passivation continues to be a significant requirement in achieving high solar-cell efficiency. Single layers of SiO2 and double layers of SiO2/SiN surface passivation have been widely used to reduce surface carrier recombination in silicon solar cells. Passivation films reduce surface recombination by a combination of chemical and electric field effect components. Dielectric films used for this purpose, however, must also accomplish optical functions at the cell surface. In this paper, field effect passivation is seen as a potential method to enhance the passivation properties of a dielectric film while preserving its optical characteristics. It is observed that the field effect can make a large reduction in surface recombination by using corona charged ions deposited on the surface of a dielectric film. The effect is studied for both SiO2 and SiO2/SiN layers, and surface recombination velocities of less than 9 cm/s and 16 cm/s are inferred, respectively, on n-type, 5 cm, Cz-Si. This improvement in passivation was stabilized for period of over a year by chemically treating the films to prevent water absorption. Intense ultraviolet radiation was seen to diminish the surface recombination velocity to its initial value in a time period of up to 7 days. Additionally, external deposition of charge on to the SiO2/SiN passivated front surface of back-contact n-type silicon solar cells provides a 2.5 % relative improvement in conversion efficiency due to enhanced and controlled field effect passivation.